Intracranial Metastases Tend to Be Overt and Predict Poor Prognosis in Children With Neuroblastoma - Liu, Ying; Huo, Liang; Zhang, Jinhua; Liu, Ying (Frontiers in Pediatrics, 2021)
Background: Neuroblastoma (NB) is the most common pediatric extracranial solid neoplasm after leukemia. Intracranial metastases (IM) rarely occur in patients with NB. The present study aimed to review the clinical characteristics of NB patients from a single center presenting with IM. Methods: Two hundred children (aged 3–91 months) with NB admitted to the Fourth Affiliated Hospital of China Medical University between January 2009 and December 2015 were enrolled, and their clinical characteristics were recorded. The patients were divided into two groups based on the presence of IM. Their clinical characteristics, including demographics, clinical features, and laboratory and imaging studies, were retrospectively analyzed. Results: IM occurred in 22 of 200 (11%) neuroblastoma patients, with a median age of 42.5 months (range, 3–91 months), with a male to female ratio of 1.4:1. Seven patients had IM at the initial diagnosis. Among the 15 children who did not have IM at initial presentation, the median interval from presentation to the diagnosis of IM was 17.3 months (range, 1–55 months). Compared with the control group, NB patients with IM tended to be asymptomatic at the time of NB diagnosis, which was made incidentally during routine physical examination (5 of 22, 22.7%, P<0.05). In addition, this group had more primary intra-abdominal sites (18 of 22, 81.8%, P<0.001) and worse prognosis (5 of 22, 22.7%, P<0.05). Conclusions: NB patients with IM have insidious onset in the early stage and a lower survival rate, especially patients with primary intra-abdominal lesions. Regular neurological monitoring could improve the rate of early diagnosis and prognosis of NB children with IM. Familiarity with the characteristic findings of NB with IM is necessary to avoid misdiagnosis and initiate necessary interventions.